Effect of hydraulic retention time on pollutants removal from real ship sewage treatment via a pilot-scale air-lift multilevel circulation membrane bioreactor. (December 2019) - Cai, Yuhang; Li, Xin; Zaidi, Asad A.; Shi, Yue; Zhang, Kun; Feng, Ruizhe; Lin, Aqiang; Liu, Chen
Abstract: Developing a real ship sewage treatment system that not only satisfies the requirement of small space onboard but also meets the latest emission standards of International Maritime Organization (IMO) is still a challenging task for ship industry. To overcome these problems, in this study, a novel pilot-scale air-lift multilevel circulation membrane bioreactor (AMCMBR) was used to explore the effect of hydraulic retention time (HRT) on effluent chemical oxygen demand (COD) and total nitrogen (TN) while treating real ship sewage. Results indicated that the satisfactory removal efficiencies of COD and TN was achieved in the former stages (Re(COD) = 91.57% and 87.82%; Re(TN) = 77.17% and 81.19%). When HRT decreased to 4 h, the removal efficiencies of COD and TN was 86.93% and 70.49% respectively, which still met the strict IMO discharge standards. This mainly because the biofilm-assistant membrane filtration lead to the increase of physical removal rate. The high ratio of mixed liquor volatile suspended solids (MLVSS)/mixed liquid suspended solids (MLSS) (i.e. 0.75) indicated a high biomass content in the attached sludge and resulted into perfect pollutants removal effort. The compliance rate of COD and TN was 100% and 89%, respectively, which indicated stable operation of the pilot-scale AMCMBR throughout the whole experiment. Fluorescence in situ Hybridization (FISH) analysis revealed that the abundance of β-Proteobacteria was a key microbial reason for TN removal. In addition, wavelet neural network (WNN) model was proved to be suitable to simulate and predict the COD and TN removal. These conclusions indicated that the pilot-scale AMCMBR technology is an effective way for real ship sewage treatment. Graphical abstract: Image 1 Highlights: The pilot AMCMBR system achieved better COD and TN removal efficiency. High value of MLVSS/MLSS in the attached sludge presented in this study. FISH analysis revealed that the abundance of β-Proteobacteria has more impact on the TN removal. WNN model contributes to ensure the long-term stable operation of the sewage treatment system. Biofilm-assistant membrane filtration lead to the increase of physical removal rate under low HRT.